A late Holocene subfossil Atlantic white cedar tree-ring chronology from the northeastern United States. (15th January 2020) - Pearl, Jessie K.; Anchukaitis, Kevin J.; Donnelly, Jeffrey P.; Pearson, Charlotte; Pederson, Neil; Lardie Gaylord, Mary C.; McNichol, Ann P.; Cook, Edward R.; Zimmermann, George L.
Abstract: Tree-rings provide precise annually dated climate information, but their application can be limited by the relatively short lifespan of many trees. To overcome this limitation, tree-ring records can be extended over longer time periods by connecting living trees with older "sub-fossil" trees, which can provide information on longer timescales throughout the Holocene. These long chronologies are proxy records of past climate, provide precise chronological information for extreme events, and give insight into the range of natural climate variability prior to the instrumental period. In the densely populated northeastern United States, few tree-ring records are longer than 500 years, and there are no millennial-length tree-ring chronologies for the region. Here, we use a combination of standard dendrochronological and radiocarbon techniques, including use of the 774 CE radiocarbon excursion, to generate an absolutely dated 2500 year-long tree ring record from living, archaeological, and subfossil Atlantic white cedar ( Chamaecyparis thyoides ) found in the coastal northeastern United States. Our chronology demonstrates the potential to develop multi-millennial Chamaecyparis thyoides tree-ring records to address previously unanswered questions regarding late Holocene hydroclimate, extreme events, and temperature variability in New England. Highlights: Sub-fossil Atlantic white cedar is preserved along the northeastern U.S. coast. Distinct sub-fossil Atlantic white cedar chronologies crossdate with each other. Global radiocarbon excursions are used to date floating tree-ring chronologies. Multi-millennial tree-ring records from the Northeastern U.S. are possible.